Acceptance and Commitment Therapy on Depression of Pulmonary Tuberculosis Patient: An Intervention Based on the Health Belief Model - Gevi Melliya Sari; Muhammad Amin; Laily Hidayati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: Depression is a psychological disorder often experienced by patients undergoing tuberculosis treatment. The purpose of this study was to determine the effect of acceptance and commitment therapy based on the health belief model on the depression of pulmonary tuberculosis patients. Methods: This research used a quantitative quasi-experiment design with pre-posttest control group design. There were 56 respondents in this study selected using consecutive sampling among the Primary Healthcare Center in Sidoarjo district. The independent variables were acceptance and commitment therapy based on the health belief model. The dependent variable was depression. Measurement of depression used the Beck Depression inventory II questionnaire. Analysis of the data in this study used the Wilcoxon Signed Rank Test and Mann-Whitney U Test. Results: The results showed that the treatment group p=0.000 (p<0.05) and control group p=0.000 (p<0.05), but the delta of the treatment group higher than the control group (delta: -9.79). There were differences in depression values obtained between the treatment group and the control group p=0.001 (p<0.05). Conclusion: Acceptance and commitment therapy based on the health belief model given four sessions for 30-45 minutes each session can lower depression level in pulmonary tuberculosis patients rather than a single intervention of health education. This intervention can be used by nurses to help pulmonary tuberculosis patients overcome psychological problems during treatment.